Clinicopathological Study of Parapharyngeal Space Tumor (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To see the mode of presentation, diagnosis and management of parapharyngeal space tumours.Study design: Cross sectional study.Setting: Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh.Methods: The condition being relatively rare, it was difficult to find good number of fresh cases. We have studied all cases of parapharyngeal space tumour attending in the Bangabandhu Sheikh Mujib Medical University from January 2010 to March 2011.Result: Parapharyngeal space tumours are rare head and neck neoplasms.The third decade of life showed greatest incidence. The main presenting complaint’s were painless neck swelling (73%). The highest number of pathology were attached to the deep lobe of parotid gland (pleomorphic adenoma-27%) and then neurofibroma (20%). Of all cases 77% were benign. Their accurate diagnosis and management is challenging.Bangladesh J Otorhinolaryngol; April 2017; 23(1): 41-46